De "terras do monge" a terras de "gafanhotos de aço": a expansão da monocultura e alterações socioambientais na região de Xanxerê (1970-1980) - Benetti, Tiago João (2019)
The reflections proposed in this study aim to foment the debate about the social and environmental alterations through the expansion of monocultures in the city of Xanxerê - Santa Catarina, between the 1970s and 1980s. As theoretical support of this study, is analyzed the General Plan of land characterization of the city of Xanxerê - INCRA (1974), with data and information about the land situation in that period in this region. In this sense, a comparation is made with historical data of agrarian productivity and expansionism, available by the responsible governmental agencies, in addition to verifying the activity of the governmental instruments used, focusing on the analysis of the documents mentioned above and on the existing bibliography. Another tool used in this study is the comparison and overlay of images and information from the Support Vector Machine (SVM) system in ENVI software, which allows to verify the expansionism of monocultures and transformations in the local environment. In this proposal, it is used the language figure from “monk's lands” to “steel locusts” lands to verify the social and environmental changes that these localities have suffered over the most recent decades. In this way, it is seeks to approach the image of locusts to modern agricultural harvesters and pesticide sprayers, including the shape or silhouette of these machines, very close to the description of the insect reported by the Monge do Contestado (Contested Monk), which modify the environment where they are. It also seeks to understand the factors that made the study region become an agricultural granary and what are the reflections on the local economic and environmental situation, as well as the instruments used in this endeavor.